A Sliding Mode Controller Design for Buck Converters in Robotic Power Systems - Al-Ataby, Ali; Attia, Hussain (Engineering, Technology & Applied Science Research, 2025)
Robotic power systems rely on buck converters to step down voltages and supply regulated DC voltages to sensors, controllers, and actuators, hence they are essential for the stable and efficient operation of robotic systems. However, maintaining an accurate output voltage under changing loads and battery conditions requires robust, non-conventional control strategies in robotics. This paper proposes the use of a Sliding Mode Controller (SMC) to control the buck converter output voltage in robotic applications. The proposed SMC is designed to maintain a reference voltage of 25 V accurately across changing load conditions. MATLAB/Simulink has been used as the simulation environment to confirm the controller’s effectiveness, and the results show that the SMC is superior in reducing overshoot, limiting voltage fluctuations from 30–35 V (in the constant duty cycle case) to a narrow range of 25–25.5 V, and maintaining accuracy under dynamic power requirements. The findings confirm the potential of the proposed control mechanism to improve energy efficiency and reliability in robotic applications, particularly for robotic manipulators, mobile robots, and autonomous systems in general.